High Quality Color Image Compression using DWT and Multi-level Block Partition Encoding-Decoding Technique - Kulthe, Manjusha Gulabrao; Jaiswal, Priyanka; Chourasia, Bharti (International Journal of Computer Sciences and Engineering, 2019)
Text and image data are important elements for information processing almost in all the computer applications. Uncompressed image or text data require high transmission bandwidth and significant storage capacity. Designing and compression scheme is more critical with the recent growth of computer applications. Among the various spatial domain image compression techniques, multi-level Block partition Coding (ML-BTC) is one of the best methods which has the least computational complexity. The parameters such as Peak Signal to Noise Ratio (PSNR) and Mean Square Error (MSE) are measured and it is found that the implemented methods of BTC are superior to the traditional BTC. This paves the way for a nearly error free and compressed transmission of the images through the communication channel.